60 Patients Admitted to Hospital with a Diagnosis of Atrial Fibrillation Outside of Standard Weekday Working Hours and At Weekends Have Worse Mortality and Poorer Survival. (3rd June 2016) - Carter, Paul R; Reynolds, Jennifer; Uppal, Hardeep; Chandran, Suresh; Sarma, Jaydeep; Potluri, Rahul
Abstract : Introduction: Atrial fibrillation (AF) is the most common cardiac arrhythmia and is associated with serious sequelae such as stroke and a significant mortality rate. Timely and optimal treatment of this condition can minimise these complications. There is evidence that patients with a range of conditions admitted out-of-hours (during evenings and weekends) have worse mortality compared to patient admitted during standard working hours. Mortality rates of AF patients admitted out of hours in the UK have not been previously been studied. We therefore aimed to study the impact of day and time of admission on short and long-term mortality in patients with AF. Methods: Anonymous data was collected from all patients with a diagnosis of AF admitted to several NHS hospitals in the North of England from 1 st January 2000 to 31 st March 2013 using the ACALM study protocol. The primary outcome of the study was "in and out of hospital mortality" within 30 days, 1 year, 5 years after the index admission. Results: 929, 552 patients were admitted, of which 42, 687 (4.6%) patients had AF. 18, 732 (43.9%) of these were admitted during normal working hours (0900–1700; Monday-Friday) and 23, 955 (56.1%) were admitted out of hours. Unadjusted crude mortality rates of patients admitted out of hours (539/1000) were higher than those admitted during normal working hours (489/1000). Unadjusted crude death rates of patients admitted on Saturday (588/1000) and Sunday (548/1000) were significantly higher than other days of the week (Figure 1 ). Cox regression analyses accounting for variations in age, gender, ethnic group and the ten most common causes of death in the UK (Listed in Table ) showed that out of hours admission with AF conferred significantly worse mortality (OR 1.12 (95%C. I 1.09–1.15) compared to admission during normal working hours. Conclusions: This study suggests a higher risk of death for patients with a diagnoses of Atrial Fibrillation admitted outside of normal hours and weekends compared with standard weekday normal working hours. The impact of our findings on service provision and healthcare delivery should to be widely debated.